Implementation of Cloud Accreditation as Accreditation Assessment Simulation in Lancang Kuning University - Bayu Febriadi; Adi Rahmat; Pandu Pratama Putra (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
SIM Accreditation Cloud is a media accreditation simulation facility that is used by the Study Program and BPM in implementing and monitoring the feasibility of the study program whether it is in accordance with the standards that should be in creating a quality culture. In the face of the Regulation of the Minister of Education and Culture (PERMENDIKBUD) No. 5 of 2020 and the regulation of the National Accreditation Board for Higher Education (BANPT) No. 1 of 2020, related to the mechanism for extending the accreditation of universities and study programs that already use the Higher Education Accreditation Instrument (IAPT 3.0) and Study Program Accreditation Instrument (IAPS 4.0), so We need a system that can help Lancang Kuning University in the preparation and implementation of accreditation assessment simulations for both universities and study programs in order to be able to adjust the implementation and preparation of the mechanism for extending the validity period of accreditation for colleges and study programs. However, the fact is that until now there has been no study program that has proposed an extension of the accreditation period using the Study Program accreditation instrument. Lancang Kuning University has 21 Study Programs consisting of 9 Faculties, in implementing an internal quality assurance system, Lancang Kuning University has a Quality Assurance Agency in charge of managing a quality culture, but in the implementation of accreditation with IAPS 4.0 this has not been effective, this is proven to be absent from the study program. who are ready to apply with IAPS 4.0, because there are still obstacles in the preparation of accreditation instruments, while the need for accreditation ratings is very much needed by study programs so that they are able to compete and realize the vision and mission of the study program.